EFFECT OF STRATEGIC HUMAN RESOURCE MANAGEMENT PRACTICES ON ORGANIZATIONAL PERFORMANCE IN THE KENYAN PUBLIC SECTOR. - Maina, Benaida (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of the study was effect of strategic human resource management practices on organizational performance in the Kenyan public sector. Methodology: The research design used a descriptive design. The target population of this study was the large manufacturing firms in Kenya which were members of Kenya Association of Manufacturers. The population was 108 large manufacturing firms. A sample size of 54 firms was taken. The study used both primary data and secondary data. Data was collected by use of questionnaire. Analysis was done by descriptive statistics using Statistical Package for Social Sciences version 21.0. Data was analyzed mainly by use of descriptive and inferential statistics. Descriptive statistics included mean and standard deviation. Data was also presented by use of graphs, pie charts and tables. Regression analysis was also used to show the sensitivity of financial performance, ROA to various independent variables. Results: Following the study findings it was possible to conclude that all the Independent variables had an effect on a company's financial performance. This was supported by majority who concluded that independent directors had a mandate to decision making in financial performance, the Independent directors effectively monitor and control firm activities by reducing opportunistic managerial behaviors and expropriation of firm resources board committees. Enhance effective monitoring in financial performance, the board committees in our firm ensures that executive directors make decisions that are in the best interests of shareholders. Coordination and communication problems impede company performance when the number of directors' increases, overcrowded boards causes shareholders to lose money in the company, the post of the chairman is part-time and the main responsibility is to ensure that the board works effectively. Regression results indicated that there was a positive and significant relationship between independent directors, board committees, board size and CEO's dual role as a company's chairman on a company's financial performance and financial performance of manufacturing firms. Unique contribution to theory, practice and policy: The study recommended that the firm should have nonexecutive directors who act as "professional referees" to ensure that competition among insiders stimulates actions consistent with shareholder value maximization, A company should have small boards so as to have more favorable performance, the appropriate board size should be 7 to 8 members and the post of the CEO/chairman should be full-time